Surveillance of human retroviruses in blood samples from patients with hepatitis B and C in São Paulo, Brazil - Adele Caterino-de-Araujo; Karoline Rodrigues Campos; Tamirez Villas Boas Petrucci; Rafael Xavier da Silva; Marcílio Figueiredo Lemos; Regina Célia Moreira (Revista da Sociedade Brasileira de Medicina Tropical)
Abstract INTRODUCTION Human retroviruses and the hepatitis B and C viruses (HBV and HCV, respectively) share routes of transmission; thus, coinfections occur and could alter subsequent disease outcomes. A preliminary study on human T-lymphotropic virus types 1 and 2 (HTLV-1/2) in serum samples from HBV- and HCV-infected individuals in São Paulo revealed 1.3% and 5.3% rates of coinfection, respectively. These percentages were of concern since they were detected in HTLV-endemic regions and in high-risk individuals in Brazil. The present study was conducted to extend and confirm these data. METHODS HTLV-1/2 and human immunodeficiency virus (HIV) infection status were identified in 1,984 sera for HBV and HCV viral load quantification - 1,290 samples from HBV-infected individuals (53.3% men, mean age: 47.1 years) and 694 samples from HCV-infected individuals (56.3% men, mean age: 50.1 years). HTLV-1/2 antibodies were detected by enzyme immunoassay, followed by western blotting and line immunoassay; HIV infection was detected by enzyme immunoassay. RESULTS HTLV-1/-2 infection was detected in 1.9% HBV-infected individuals (0.7% HTLV-1 and 1.2% HTLV-2) and in 4.0% (2.4% HTLV-1 and 1.6% HTLV-2) HCV-infected individuals; HIV infection was detected in 9.2% and 14.5%, respectively. Strong associations with HTLV and HIV, male sex, and older age were found in HBV/HTLV and HCV/HTLV-coinfected individuals (p<0.05). CONCLUSIONS HTLV-1 and HTLV-2 were confirmed to be prevalent in individuals with HBV and HCV in São Paulo; coinfected individuals deserve further clinical and laboratory investigation.